Perencanaan Tata Ruang Berwawasan Pangan: Sebuah Resep Untuk Kota Berkelanjutan - Sri Tuntung Pandangwati (REKA RUANG, 2022)
This paper aims to explore the concept of food sensitive planning which is a relatively new approach in urban and regional planning (URP) discipline. Food is one of human basic needs, but unfortunately it has been neglected in planning research and practice for a quite long time. Integrating food considerations into URP is critical because it can enhance urban/regional food security and sustainability. The integration of food and planning can be achieved through creating urban and regional spaces that enhance food availability, accessibility and utilization. The ways in which planners can improve food waste management are also discussed in this paper. In addition, this paper also discusses various research and planning topics that are related to food and planning. Hence, more research and work that integrate planning and food can be developed in the near future